Semiquantitative Computed Tomographic Characteristics for Lung Adenocarcinoma and Their Association with Lung Cancer Survival - Wang, Hua (Clin Lung Cancer, 2015)
BACKGROUND: Computed tomographic (CT) characteristics derived from noninvasive images that represent the entire tumor may have diagnostic and prognostic value. The purpose of this study was to assess the association of a standardized set of semiquantitative CT characteristics of lung adenocarcinoma with overall survival. PATIENTS AND METHODS: An initial set of CT descriptors was developed to semiquantitatively assess lung adenocarcinoma in patients (n=117) who underwent resection. Survival analyses were used to determine the association between each characteristic and overall survival. Principle component analysis (PCA) was used to determine characteristics that may differentiate histological subtypes. RESULTS: Characteristics significantly associated with overall survival included pleural attachment (p < 0.001), air bronchogram (p = 0.03), and lymphadenopathy (p = 0.02). Multivariate analyses revealed pleural attachment was significantly associated with an increased risk of death overall (hazard ratio [HR] = 3.21; 95% confidence interval [CI] 1.53 – 6.70) and among patients with lepidic predominant adenocarcinomas (HR = 5.85; 95% CI 1.75 – 19.59), while lymphadenopathy was significantly associated with an increased risk of death among patients with adenocarcinomas without a predominant lepidic component (HR = 3.07; 95% CI 1.09 – 8.70). A PCA model showed that texture (ground-glass opacity component) was most important for separating the two subtypes. CONCLUSION: A subset of the semiquantitative characteristics described herein has prognostic importance and ability to distinguish between different histological subtypes of lung adenocarcinoma.